Juridiskās zinātnes, Nr. 15, 2022 - Lazdiņš, Jānis; Osipova, Sanita; Latvijas Universitāte (University of Latvia., 2022)
The journal aims to promote dialogue among lawyers of Latvia, the European Union and other countries about relevant problematic issues in legal science and possible solutions to them within international law, European Union law, national laws, theory, philosophy, history of law and in other dogmatic sub-branches of law.
Law, No.15, 2022
The Journal of the University of Latvia
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::Jurisprudence; Research Subject Categories::LAW/JURISPRUDENCE::Public law::Constitutional law; corporate criminal liability; Basic Law; women’s rights; prevention; discrimination; Constitution; Soviet law; importance of whistleblowers; sexual harassment; humanisation of international law; Satversme (Constitution of the Republic of Latvia); minimum wage; general principles of law; violence; counterfeit; European Union law; virtual corporate seat; trade secrets; compliance; criminal procedure; public-private partnership; Doctrine 'in loco parenti'